The Clinicopathological and Prognostic Value of PD-L1 Expression in Cholangiocarcinoma: A Meta-Analysis - Xu, Gang; Sun, Lejia; Li, Yunzhu; Xie, Feihu; Zhou, Xiaoxiang; Yang, Huayu; Du, Shunda; Xu, Haifeng; Mao, Yilei (Frontiers in Oncology, 2019)
Background: Recently, blockade of immune checkpoint has emerged as one of the most potential treatments for solid tumors. Programmed cell death ligand 1(PD-L1), a member of the B7 family of molecules, plays a crucial role in tumor immunobiology. However, the prognostic significance of PD-L1 in cholangiocarcinoma (CCA) patients remains controversial. This study aimed to inquire into the prognostic and clinicopathological significance of PD-L1 in CCA via a meta-analysis. Methods: We searched PubMed, the Cochrane Library, Embase, Web of Science and Google Scholar up to April 2019, regardless of the region or language, for studies on the correlation between clinicopathology/prognosis and PD-L1 in patients with CCA. The pooled hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated to investigate the prognostic significance of PD-L1 expression in cholangiocarcinoma. The odds ratios (ORs) were also determined to explore the association between PD-L1 expression and clinicopathological features. Results: Our meta-analysis included 11 studies with 1,066 patients. The meta-analysis of these studies indicated a trend that high PD-L1 expression indicated a poor OS, but the result was not statistically significant (HR = 1.62, 95% CI [0.98–2.68], p = 0.063). For DFS, although the pooled result is not statistically significant, it trends toward being significant that high PD-L1 expression indicated improved DFS (HR = 0.80, 95% CI [0.62, 1.04], p = 0.092). In subgroup analyses, the results were not consistent across the subgroups that were divided based on the publication year (before 2018: HR = 1.92, 95% CI [1.34–2.75], p < 0.001; after 2018: HR = 1.42, 95% CI [0.70–2.89], p = 0.335). Moreover, PD-L1 expression in TCs significantly correlated with the AJCC TNM stage of CCA (OR = 0.52, 95% CI [0.27, 0.99], p = 0.09). Conclusion: Our meta-analyses revealed that PD-L1 expressed in TCs was significantly correlated with the AJCC TNM stage of CCA. Based on the included studies, we found that PD-L1 indeed expressed in both TCs and ICs in CCA patients, raising the possibility of the use of anti-PD-1/PD-L1 therapy for CCA patients. In contrast, expression of PD-L1 did not seem to be associated with patient outcome in our study. The prognostic role of PD-L1 in CCA demands further investigation.